Peran tingkat kualitas pelayanan terhadap minat nasabah dalam memilih asuransi syariah - suryati, suryati (Maliki Interdisciplinary Journal, 2024)
The aim of this research is to determine the role of service quality levels on customer interest in choosing sharia insurance. This research is quantitative research with a survey method. Good service quality greatly influences customer confidence in choosing sharia insurance products. In this study, all respondents chose sharia insurance companies with better service quality, even though the premiums offered were slightly higher. Thus, it can be seen that the quality of products provided by insurance companies is primarily responsible for the production of insurance products. Therefore, sharia insurance companies need to prioritize service quality as an important factor in retaining existing customers and attracting new customers.